Fe, Co and Ni doped MnMoO4.H2O two-dimensional porous nano material and preparation method thereof

Through the Mnmoo4 · H2O nanomaterials doped by FE, CO and Ni mixed with Ni -free water thermal method, the existing MNMOO4 electrode materials have poor capacitance and poor circulation performance during the oxidation reduction process, and realized high -level capacitors and good good capacitors and good good capacitors Cycle stability electrochemical performance.

CN119370893APending Publication Date: 2025-01-28GUIZHOU MEILING POWER SUPPLY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411333627.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

During the continuous redox process, existing MnMoO4 electrode materials have problems such as capacitance fading, low energy density, unstable structure and unsatisfactory cycling performance.

Method used

By preparing the Mnmoo4 · H2O nano -nano -pore nanomaterials mixed with FE, CO and Ni mixed with Ni -doping of FE, CO, and Ni through the conditions without surface active agents, the introduction of oxygen defects to improve electrochemical performance.

Benefits of technology

The prepared FE, CO, and Ni doped mnmoo4 · H2O nanomaterials reached 632.5C · G-1 when the current density was 1A · G-1, and the capacity maintenance rate was 93.59%after the circulation of 12,000 laps. The energy density shows good energy density and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119370893A_ABST
    Figure CN119370893A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of nano materials, in particular to a Fe, Co and Ni doped MnMoO4.H2O nano two-dimensional porous nano material and a preparation method thereof. On the basis of a defect engineering strategy, a template-free hydrothermal method is adopted, the MnMoO4.H2O nano material doped with Fe, Co and Ni is designed under the condition of no surfactant, and the influence of the type and doping amount of metal ions on the morphology and electrochemical performance of the product is explored. Wherein the metal ions can generate a large number of oxygen defects in the process of doping the MnMoO4.H2O. The defects not only can optimize a band gap and an electronic structure, but also can be used as additional active sites to participate in an oxidation-reduction reaction, so that the capacitance performance and the rate capability of an electrode material are improved. The specific capacity of the prepared oxygen-deficient nano material reaches 632.5 C.g <-1 > when the current density is 1A. G <-1 >, which is 3.4 times of that of a MnMoO4.H2O material without any metal ions doped, and the capacity retention rate after 12000 cycles is 93.59%. Besides, NMMO-5 and AC are respectively used as a positive electrode and a negative electrode to assemble the hybrid energy storage device, the energy density of the hybrid energy storage device reaches 35.1 Wh.kg <-1 >, and the capacity is still 103% of the initial capacity after 10000 times of circulation, which indicates that the hybrid energy storage device is good in circulation stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano materials, in particular to a Fe, Co and Ni doped MnMoO4·H2O nano two-dimensional porous nano material and a preparation method thereof. Background Art

[0002] In order to meet the energy needs of modern society, the development of energy storage technology is one of the most pressing issues of this century. Supercapacitors (SCs) have attracted much attention as the next generation of power storage devices due to their advantages such as safe operation, long cycle life, and high specific energy. However, the limited energy density greatly restricts the practical application of SCs. Seeking high-performance electrode materials with high energy density has become the key to preparing high-capacitance SCs devices. The performance of SCs can usually be improved through reasonable design, material selection, and preparation strategies.

[0003] As a unique class of materials with high electrochemical activity and a wide variety of characteristics, transition metal molybdates, such as FeMoO4, CoMoO4, NiMoO4, MnMoO4 and ZnMoO4, have become important candidate materials for SCs. Among them, the role of molybdenum is to improve the conductivity of transition metal molybdates, and it does not participate in redox reactions, which has great application value. In addition, transition metal molybdates have significant properties such as higher theoretical capacitance, conductivity and multiple redox reactions than single-component oxides. Moreover, MnMoO4 is considered to be an efficient electrode material due to its high theoretical capacitance, rich manganese oxidation states and large working potential window. However, MnMoO4 electrode materials still have serious capacitance fading, low energy density, structural instability and unsatisfactory cycle performance during continuous redox processes. In order to overcome these problems, researchers have found that introducing suitable metal cations and designing reasonable nanostructures are effective ways to enhance the electrochemical properties of electrode materials, which can adjust the electronic structure of the material and improve the conductivity. At the same time, the generation of oxygen defects is usually related to the doping of transition metal ions. Doping with transition metal ions provides abundant defects, which act as additional active sites to promote the diffusion of ions in the lattice, thereby promoting the electrochemical kinetics of the electrode. This has stimulated extensive exploration of different dopants in host metal molybdates. In 2020, Yuan et al. reported the preparation of Mn-doped NiMoO4 nanorods by hydrothermal method. The obtained product has smaller unit parameters and stronger reactivity than the original NiMoO4, and the electrochemical performance is better than that of the original NiMoO4 at 0.5A·g -1 The current density is 688.9F·g –1Sharma et al. synthesized a rod-shaped electrode material with good conductivity and rich oxygen defects by doping NiMoO4 with different concentrations of Zn by wet chemical method. Zn dopant enhances the surface of electrolyte and OH - It plays an important role in the transfer of charge between ions.

[0004] Among the numerous studies, few have focused on the effects of the types and doping amounts of different metal ions on the morphology and electrochemical properties of the products. Therefore, finding a Fe, Co and Ni doped MnMoO4·H2O oxygen defect nanomaterial and its preparation method, which can significantly improve the electrochemical performance of hybrid energy storage devices, is the current key research direction. Summary of the invention

[0005] In order to solve the above technical problems existing in the prior art, the present invention provides a Fe, Co and Ni doped MnMoO4·H2O nano two-dimensional porous nanomaterial and a preparation method thereof, which is specifically achieved through the following technical solutions.

[0006] A method for preparing Fe, Co and Ni doped MnMoO4·H2O nano two-dimensional porous nanomaterials is disclosed. The Fe, Co and Ni doped MnMoO4·H2O nano oxygen defect materials are prepared by a template-free hydrothermal method without a surfactant.

[0007] The method specifically comprises the following steps:

[0008] (1) First, dissolve MnCl2·4H2O in distilled water and stir (at room temperature) to obtain solution I;

[0009] (2) Dissolve Na2MoO4·2H2O in distilled water and stir (at room temperature) to obtain solution II;

[0010] (3) Take solution II and solution I separately, slowly add solution II to solution I, and stir (at room temperature) to obtain a milky white solution III;

[0011] (4) Add NiCl2·6H2O to solution III and stir to obtain solution IV;

[0012] (5) Solution IV is transferred to a stainless steel autoclave and heated for reaction; after the reaction is completed, it is cooled to room temperature (natural cooling is sufficient), taken out and filtered, washed and dried to obtain Ni-doped MnMoO4·H2O product, which is labeled as NMMO-x; the Co and Fe doping amounts are prepared according to the Ni doping method and are labeled as FMMO-x and CMMO-x.

[0013] Furthermore, the step (1) is specifically to take 3.4-4 mmol MnCl2·4H2O and dissolve it in 40-60 ml distilled water.

[0014] Furthermore, the stirring in steps (1), (2) and (3) is magnetic stirring at a stirring speed of 400 to 700 rpm for 20 to 40 min.

[0015] Furthermore, the step (2) is specifically to take 4 mmol·Na2MoO4·2H2O and dissolve it in 40-60 ml of distilled water.

[0016] Furthermore, in step (3), the volume ratio of solution II to solution I is (4-6):(4-6), specifically 40-60 ml of solution II and 40-60 ml of solution I.

[0017] Furthermore, in step (4), 0-0.6 mmol NiCl2·6H2O is added to solution III, and stirring is continued for 40-80 min.

[0018] Furthermore, the heating in step (5) is performed at 160 to 220° C. for 6 to 10 hours at a heating rate of 8 to 12° C. / min.

[0019] Furthermore, the washing in step (5) is performed by alternately rinsing with distilled water and ethanol, and the number of rinsing times is preferably 3 times.

[0020] Furthermore, the drying is carried out at 40 to 80° C. for 8 to 16 hours:

[0021] Furthermore, in the NMMO-x, x is Ni doping amount of 0%, 2.5%, 5% and 7.5%; in Co and Fe doping amount, x is 5%.

[0022] Furthermore, the total amount of the MnCl2·4H2O and transition metal salts (FeCl2·4H2O, CoCl2·6H2O, NiCl2·6H2O) was always maintained at 4 mmol, and other conditions were not changed.

[0023] The Fe, Co and Ni doped MnMoO4·H2O nano two-dimensional porous nanomaterial is prepared by the above-mentioned preparation method of Fe, Co and Ni doped MnMoO4·H2O nano two-dimensional porous nanomaterial.

[0024] Compared with the prior art, the technical effects created by the present invention are embodied in:

[0025] (1) Based on the defect engineering strategy, this paper adopts a template-free hydrothermal method to design Fe, Co and Ni doped MnMoO4·H2O nanomaterials in the absence of surfactants, and explores the effects of the type and amount of metal ions on the morphology and electrochemical properties of the products. Among them, a large number of oxygen defects will be generated during the process of doping MnMoO4·H2O with metal ions. In addition to optimizing the band gap and electronic structure, these defects can also participate in redox reactions as additional active sites, thereby improving the capacitance and rate performance of electrode materials. The prepared oxygen defect nanomaterials have a high capacitance at a current density of 1A·g -1 The specific capacity reached 632.5C·g -1 , which is 3.4 times that of MnMoO4·H2O material without any metal ion doping, and the capacity retention rate after 12,000 cycles is 93.59%. In addition, NMMO-5 and AC are used as positive and negative electrodes respectively to assemble a hybrid energy storage device, and its energy density reaches 35.1Wh·kg –1 , after 10,000 cycles, the capacity is still 103% of the initial capacity, indicating that the hybrid energy storage device has good cycle stability.

[0026] (2) The present invention is an effective method to improve electrochemical performance by doping transition metals and introducing oxygen defects. The obtained NMMO-5 can be used as a promising SCs electrode material. Different transition metal doping can affect the morphology of MnMoO4·H2O and improve the specific capacitance and cycle stability of MnMoO4·H2O. The electrochemical experimental results show that when the nickel doping concentration is 5%, the specific capacitance of the NMMO-5 electrode is improved the most and the cycle performance is the best. At 1A·g -1 At a current density of 1.34 W, the specific capacitance of the NMMO-5 electrode is 632.5 C·g -1 Much larger than the specific capacitance of the original MMO (184.5C g -1 After 12,000 cycles, the specific capacity of NMMO-5 can still maintain a capacity retention rate of 93.59%. In 2MKOH, the HSC assembled with NMMO-5 as the positive electrode and AC as the negative electrode has a wide operating voltage of 1.5V, and when the power density is 750W·kg -1 The energy density is 35.1Wh·kg -1 And after the capacitor is cycled 10,000 times, it still has a specific capacity retention rate of 103%. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the preparation flow chart of MnMoO4·H2O doped with different transition metals.

[0028] Figure 2(a) XRD patterns and (b) XPS spectra of each product.

[0029] Figure 3 (a) Fe 2p of FMMO-5; (b) Co 2p of CMMO-5; (c) Ni 2p, (d) Mn 2p, (e) Mo 3d of NMMO-5 and (f) O1s spectra of each product.

[0030] Figure 4 It is the N2 adsorption-desorption isotherm of NMMO-5 and the corresponding BJH pore size distribution diagram.

[0031] Figure 5 are SEM images of (a) MMO, (b) FMMO-5, (c) CMMO-5, (d) NMMO-2.5, (e) NMMO-5 and (f) NMMO-7.5 products.

[0032] Figure 6 (a) The sample is at 60mV·s -1 CV curves of NMMO-5 (b) at different scan rates; (c) the functional relationship between the cathode and anode peak currents and the square root of the scan rate; (d) the linear relationship between log(i) and log(v); (e) 10 mV·s -1 Capacitance contribution under (f) and capacitance contribution ratio under various scan rates.

[0033] Figure 7 (a) The product is 6·A·g -1 GCD curves of NMMO-5 at different current densities; (b) GCD curves of NMMO-5 at different current densities; (c) Specific capacities of each electrode at different current densities; (d) Specific capacities of NMMO-5 electrode at 10 A·g -1 Cyclic stability under .

[0034] Figure 8 (a) Schematic diagram of the assembled NMMO-5 / / AC device; (b) scanning rate of 40 mV·s -1 CV curves of AC and NMMO-5 electrodes; NMMO-5 / / AC device (c) at different voltage windows with a scan rate of 40 mV·s -1 CV curves of (d) 4A·g -1 (e) GCD curves at different scan rates, and (f) GCD curves at different current densities.

[0035] Fig. 9 (a) Ragone plots of the NMMO-5 / / AC device and some recent work; (b) at 10A·g -1 Cycle performance under . DETAILED DESCRIPTION

[0036] The technical solution of the present invention is further defined below in conjunction with specific implementation methods, but the scope of protection required is not limited to the description.

[0037] Preparation of MnMoO4·H2O doped with different transition metals:

[0038] Example 1 (5% Ni doping):

[0039] (1) First, 3.6 mmol of MnCl2·4H2O was weighed and dissolved in 50 ml of distilled water. The mixture was magnetically stirred at 500 rpm for 30 min at room temperature to obtain solution I.

[0040] (2) Weigh 4 mmol Na2MoO4·2H2O and dissolve it in 50 ml distilled water. Stir the mixture under magnetic stirring at 500 rpm for 30 min at room temperature to obtain solution II.

[0041] (3) 50 ml of solution II and 50 ml of solution I were measured respectively, and solution II was slowly added to solution I, and magnetic stirring was performed at room temperature at a stirring speed of 500 rpm for 30 min to obtain a milky white solution III;

[0042] (4) Add 0.4 mmol NiCl2·6H2O to solution III and continue stirring for 60 min to obtain solution IV;

[0043] (5) Solution IV was transferred to a stainless steel autoclave and heated at 180°C for 8 h at a heating rate of 10°C / min. After the reaction was completed, it was naturally cooled to room temperature, taken out and filtered, and rinsed with distilled water and ethanol alternately three times, and dried at 60°C for 12 h to obtain the Ni-doped MnMoO4·H2O product, which was labeled as NMMO-5.

[0044] Example 2 (5% Co doping):

[0045] (1) First, 3.6 mmol MnCl2·4H2O was weighed and dissolved in 50 ml distilled water, and the mixture was magnetically stirred at 500 rpm for 30 min at room temperature to obtain solution I;

[0046] (2) Weigh 4 mmol Na2MoO4·2H2O and dissolve it in 50 ml distilled water. Stir the mixture under magnetic stirring at 500 rpm for 30 min at room temperature to obtain solution II.

[0047] (3) 50 ml of solution II and 50 ml of solution I were measured respectively, and solution II was slowly added to solution I, and magnetic stirring was performed at room temperature at a stirring speed of 500 rpm for 30 min to obtain a milky white solution III;

[0048] (4) Add 0.4 mmol CoCl2·6H2O to solution III and continue stirring for 60 min to obtain solution IV;

[0049] (5) Solution IV was transferred to a stainless steel autoclave and heated at 180°C for 8 h at a heating rate of 10°C / min. After the reaction was completed, it was naturally cooled to room temperature, taken out and filtered, and rinsed with distilled water and ethanol alternately three times, and dried at 60°C for 12 h to obtain the Co-doped MnMoO4·H2O product, which was labeled as CMMO-5.

[0050] Example 3 (5% Fe doping):

[0051] (1) First, 3.6 mmol MnCl2·4H2O was weighed and dissolved in 50 ml distilled water, and the mixture was magnetically stirred at 500 rpm for 30 min at room temperature to obtain solution I;

[0052] (2) Weigh 4 mmol Na2MoO4·2H2O and dissolve it in 50 ml distilled water. Stir the mixture under magnetic stirring at 500 rpm for 30 min at room temperature to obtain solution II.

[0053] (3) 50 ml of solution II and 50 ml of solution I were measured respectively, and solution II was slowly added to solution I, and magnetic stirring was performed at room temperature at a stirring speed of 500 rpm for 30 min to obtain a milky white solution III;

[0054] (4) Add 0.4 mmol FeCl2·4H2O to solution III and continue stirring for 60 min to obtain solution IV;

[0055] (5) Solution IV was transferred to a stainless steel autoclave and heated at 180°C for 8 h at a heating rate of 10°C / min. After the reaction was completed, it was naturally cooled to room temperature, taken out and filtered, and rinsed with distilled water and ethanol alternately three times, and dried at 60°C for 12 h to obtain the Fe-doped MnMoO4·H2O product, which was labeled as FMMO-5.

[0056] Preparation of working electrode

[0057] (1) Pretreatment of nickel foam: First, cut the whole piece of nickel foam into 1×1 cm 2. Then, treat with acetone and dilute hydrochloric acid for 0.5h respectively. Then, wash thoroughly with anhydrous ethanol several times and keep warm at 80℃ for 12h. Finally, weigh the nickel foam and record its mass for later use;

[0058] (2) Slurry preparation: According to the mass ratio of active material: conductive agent: binder of 7:2:1, weigh and grind thoroughly, and slowly add an appropriate amount of NMP solvent drop by drop. After ultrasonication for 30 minutes, a uniform viscous paste slurry is formed, which is set aside;

[0059] (3) Coating: The prepared slurry is evenly coated on the nickel foam, which is then placed in a vacuum drying oven at 60°C for 12 h to obtain an electrode;

[0060] (4) Weighing: The electrodes were weighed, and the loading amount of active material was calculated by the difference in mass of nickel foam before and after coating. The loading amounts of MMO, FMMO-5, CMMO-5, NMMO-2.5, NMMO-5, and NMMO-7.5 were 1.12, 1.05, 1.12, 0.98, 1.19, and 0.91 mg, respectively.

[0061] Preparation and Characterization of Physical and Chemical Properties of Oxygen-Deficient Nanomaterials Doped with Different Transition Metals

[0062] (1) XRD and XPS analysis

[0063] like Figure 2 For the phase composition and element state analysis of XRD and XPS products. Figure 2 a It can be seen that the diffraction peaks of MMO at 13.0°, 15.9°, 18.9°, 26.2°, 31.7° and 32.0° correspond to the (001), (010), (021), (110), (-210) and (111) crystal planes of MnMoO4·H2O (JCPDS No.78-0220), respectively, and no other impurity peaks appear. In addition, it can be found that the diffraction peaks of the six products are very similar, with no obvious differences. It may be that the doping content is too low and cannot be reflected in the XRD spectrum. Therefore, the XRD pattern alone cannot be used as a basis for determining whether an element is successfully doped. Fortunately, combined with the full XPS spectrum of the product Figure 2 (b), the effective doping of transition metals can be confirmed.

[0064] Figure 3 (a), (b) and (c) show the peaks associated with the doping elements, respectively. The Fe 2p spectrum has two double peaks at 724.5 eV and 711.3 eV, which belong to Fe 2p 1 / 2 and Fe 2p 3 / 2 After deconvolution, the peaks at 724.4 eV and 711.3 eV, with a combined energy gap of 13.1 eV, can be attributed to Fe2+ Oxidation state. The two peaks with higher binding energies at 727.6eV and 714.8eV represent Fe 3 + In addition, two vibration satellite peaks can be identified at 732.1eV and 719.3eV. The above characteristics indicate that there is Fe 2+ and Fe 3+ The high-resolution Co2p spectrum has two fitting peaks at 797.5eV and 781.6eV, which are Co2p 1 / 2 and Co 2p 3 / 2 , the binding energy gap is 16.1eV, and there are two satellite peaks at 787.3eV and 803.5eV. The above characteristics indicate that CMMO-5 contains Co 2 + . Figure 3 (c) is the XPS spectrum of Ni 2p, showing that Ni 2p 1 / 2 With Ni 2p 3 / 2 The binding energies of Ni are 874.1eV and 856.5eV respectively, the distance between the two binding energy peaks is 17.6eV, and there are two satellite peaks at 880.3eV and 862.4eV respectively. These characteristic peaks belong to Ni 2 + , proving that Ni replaced part of the Mn position through doping. Figure 3 .3(d) shows two peaks with binding energies of 653.5 eV and 641.9 eV, corresponding to Mn 2p 1 / 2 and Mn 2p 3 / 2 The binding energy peaks of Mn 2p are separated by 11.6 eV, indicating that the elemental valence state of Mn is +2. In addition, the peak with a binding energy of 645.7 eV is a characteristic peak of oxidized Mn. Figure 3 (e) is the XPS spectrum of Mo 3d. The binding energy peak at 232.2 eV corresponds to Mo 3d 5 / 2 energy level, and the binding energy peak at 235.3 eV corresponds to the Mo 3d 3 / 2 The main binding energy peaks of the two are 3.1eV apart, which is Mo 6+ The XPS spectra of O1s of all samples show ( Figure 3 (f)), O1s all show three peaks. The peak at 530.5 eV represents the metal-oxygen bond, the peak at 531.5 eV corresponds to the oxygen defect, and the peak at 532.9 eV corresponds to the OH bond. The intensity of oxygen defect in NMMO-5 is the highest, which indicates that Ni doping increases the concentration of MMO oxygen defects, which is beneficial to accelerate electron transfer and improve conductivity, thereby enhancing the redox reactivity of NMMO-5.

[0065] (2) BET analysis

[0066] The specific surface area and pore size distribution of NMMO-5 were studied by N2 adsorption-desorption method. Figure 4 The isotherm curve of the product shown in the figure shows a type IV with a hysteresis loop. The reason for the hysteresis is the capillary condensation adsorption phenomenon caused by the mesopores in the material during the test, indicating that the material has a mesoporous structure. In addition, Figure 4 The illustration in the figure is the pore size distribution diagram of NMMO-5. It can be seen that only a few pores are larger than 50 or even 100 nm, and the pore size is mainly distributed between 3 and 50 nm. The specific surface area of ​​NMMO-5 is 58.12 m 2 g -1 , pore volume is 0.26cm 3 g -1 and an average pore size of 11.86 nm, which increases the contact area with the electrolyte, provides abundant active sites for electrochemical reactions, and shortens the diffusion distance for charge / ion transport, thereby improving the electrochemical performance.

[0067] (3) SEM and TEM analysis

[0068] The morphology and microstructure of the product were preliminarily studied using SEM. Figure 5 As shown in (ac), SEM images of MMO, FMMO-5, and CMMO-5 at the same resolution are given. It can be clearly observed that the MMO nanostructure after metal doping shows obvious morphological changes. FMMO-5 is a "daisy"-shaped nanostructure self-assembled from nanoplates; CMMO-5 is a three-dimensional porous structure formed by disordered interweaving of two-dimensional nanosheets; NMMO-2.5, NMMO-5, and NMMO-7.5 all present nanosheet arrays with orderly arrangement, uniform size, and sharp edges. This unique structure combines the advantages of vertically arranged structure and three-dimensional independent structure. Figure 5 (df) It can be seen that as the Ni doping amount increases from 2.5% to 7.5%, the morphology of nickel-doped manganese molybdate does not change significantly. The gap between the nanosheets is too small and the ion channels are blocked, which will affect the permeability of the electrolyte and thus the electrochemical performance of the electrode material. The NMMO-5 nanosheets are stacked in an interlaced manner to form a porous nanostructure, which is consistent with the results of the N2 adsorption and desorption curve. This is conducive to making full use of the nanosheets, enhancing the charge transport kinetics, and facilitating the acquisition of active substances. In addition, the closed space composed of these orderly stacked nanosheets can be used as a micro-reservoir to store electrolytes to ensure the continuous progress of electrochemical reactions.

[0069] Electrochemical testing of materials

[0070] 1. The CV, GCD, cycle stability and EIS of MMO and doped MMO were tested using a three-electrode system.

[0071] (1) CV analysis

[0072] Figure 6 (a) Six electrode materials in 2M KOH solution at a scan rate of 60 mV·s –1 and CV curves under the conditions of potential window of -0.1-0.5V. It can be seen from the curve that the CV curve of doped transition metal is similar to the CV curve of undoped MMO, and both show typical redox peaks, indicating that the prepared material has Faraday capacitance behavior, and the charge storage is carried out through internal redox reactions, and it is a battery-type material. At the same scan rate, the specific capacitance of the electrode is proportional to the scan area of ​​the CV curve. The integral area of ​​the CV curve and the corresponding current density of the transition metal-doped MMO electrode are greater than the peak current of the undoped MMO electrode. This may be because the incorporation of transition metals enhances the conductivity and redox reaction activity of MMO, which is basically consistent with the results reported in the literature. During the entire reaction process, the OH in the electrolyte - With Mn 2+ Due to its multivalent state, Mo undergoes Faradaic reactions or proton “insertion and extraction”. Under alkaline conditions, Mo with a small electronic contribution does not participate in electrochemically active redox reactions, but can provide conductivity to improve the electrochemical properties of electrode materials.

[0073] In addition, compared with the other five electrode materials, the closed area of ​​the CV curve of NMMO-5 is the largest, indicating that the NMMO-5 electrode can store more charge and has better electrochemical performance.

[0074] In 10-100mV·s –1 CV tests were performed on NMMO-5 electrode materials at different scan rates within a range of 2. Figure 8 As can be seen in (b), the peak current of the redox peak gradually increases with the increase of the scan rate, but the shape of the electrode curve remains basically consistent without obvious distortion, indicating the quasi-reversibility of the redox couple. Figure 6 (c) shows the cathodic and anodic peak current densities of the NMMO-5 electrode as a function of the corresponding square root of the scan rate. The fitting coefficient R 2 are 0.98 and 0.97, respectively, indicating that the two have a good linear relationship, proving that the NMMO-5 electrode is a typical diffusion-controlled battery behavior. To further understand the capacitance contribution of the electrode, Figure 6 (e) shows the NMMO-5 electrode at 10 mV·s –1 Obviously, 72% of the contribution of diffusion control comes from diffusion control, which is beneficial for NMMO-5 to penetrate OH – .also, Figure 6(f) describes the electrode at 10, 20, 40, 60, 80, and 100 mVs –1 The contribution percentages of diffusion control and pseudocapacitive control processes under the same conditions are shown in Figure 2. As the scan rate increases, the diffusion control contribution gradually decreases. This is because at high scan rates, the internal resistance and polarization become larger, and the movement of ions is restricted, so that the electrolyte ions do not have enough time to enter the interior of the material. Therefore, they can only reach the electrode surface, resulting in a decrease in the diffusion-controlled current contribution.

[0075] (2) GCD test

[0076] Figure 7 (a) Comparison of six nanomaterials at 6A·g -1 The results of the GCD test in the voltage test range of 0-0.4V at a current density of 1.5V show that the GCD curves of all products have a clear charge and discharge platform and good symmetry. This is consistent with the conclusion drawn from the CV graph and basically conforms to the behavioral characteristics of battery-type materials. The charge and discharge time and integrated area of ​​the NMMO-5 material are better than those of other electrode materials, which means that this material has a larger specific capacitance. The specific capacity of the NMMO-5 electrode at different current densities is shown in Figure 2. Figure 7 As shown in (b), it is known through calculation that the NMMO-5 electrode has a high conductivity at 1, 2, 4, 6, 8 and 10 A·g -1 The specific capacities at current densities of 632.5, 630.5, 545.8, 487.3, 451.7 and 414.1 C·g -1 It can be found that the capacitance of the electrode decreases with the increase of current density. This is because the redox reaction provides a short diffusion time for the ions in the electrolyte, which is not enough to fully enter the electrode material and react with it to produce polarization. Even so, when the current density increases from 1 to 10 A·g -1 When the specific capacity of the NMMO-5 electrode is still maintained at 65.2% of the original, indicating its good rate performance. One of the reasons why the material has good electrochemical performance is the adjustment of the material morphology. The overall morphology of the NMMO-5 electrode is composed of uniformly dispersed nanosheets self-assembled into a hierarchical structure, which reduces the spacing between the nanosheets. In addition, the oxygen defects caused by Ni doping can not only serve as a carrier to improve the conductivity of the electrode material, but also may become active sites for ion diffusion and exchange to promote electrochemical reactions. In addition, the specific capacity of other samples was also calculated ( Figure 7 (c)). Table 1 compares the electrochemical properties of manganese molybdate materials and their composites.

[0077] Table 1 The electrochemical performance of the NMMO-5 electrode designed in this work is compared with those reported previously

[0078]

[0079]

[0080] (3) Cyclic performance test

[0081] The cycling stability of electrode materials is a necessary condition for practical applications. Figure 7 (d) shows the NMMO-5 at 10 A·g -1 Test results after charge and discharge cycles under different conditions. As can be seen from the figure, with the increase in the number of charge and discharge cycles, the capacity value of the sample becomes smaller and smaller, which is caused by the irreversible redox reaction of the material and the shedding of active substances during the cycle, as well as the change in electrolyte concentration during long-term testing. After 12,000 cycles, the capacity of NMMO-5 lost 6.41%, and the coulombic efficiency has been close to 100%, indicating that NMMO-5 nanosheets have good cycle stability and electrochemical reversibility during the charge and discharge process.

[0082] 2. Electrochemical performance test of NMMO-5 / / AC energy storage device

[0083] (1) CV and GCD test of NMMO-5 / / AC

[0084] In order to evaluate the application potential of NMMO-5 two-dimensional porous nanostructures in energy storage devices, such as Figure 8 As shown in (a), a hybrid energy storage device based on NF-loaded AC and NMMO-5 (NMMO-5 / / AC) was assembled in 2M KOH electrolyte with cellulose paper as the separator. Figure 8 (b) AC and electrode NMMO-5 at 40 mV·s -1 The CV curves of the former are shown in the potential window of -1-0V, while the latter shows a pair of ideal redox peaks, indicating its electrochemical stability in the voltage range of -0.1-0.5V. Compared with a single material, the combination of the two can broaden the voltage window of SCs. In order to determine the voltage window of the NMMO-5 / / AC device during electrochemical reaction, Figure 8 (cd) NMMO-5 / / AC device at 0-1.2 V to 0-1.6 V at a scan rate of 40 mV·s –1 CV curves and 4A·g -1 It can be seen from the GCD curve under the potential of 1.6V that the CV and GCD curves show obvious changes due to the severe polarization of the electrode material. Therefore, considering that the device can operate effectively, the voltage window is finally determined to be 0-1.5V. Figure 8(e) shows the CV curves at different scan rates, which all show a combination of the quasi-rectangular peaks of EDLCs-type electrodes and the redox peaks of PCs-type electrodes. Similar CV curves can be obtained at various scan rates, indicating that the device has good electrochemical reversibility. Figure 8 (f) is the GCD curve of the NMMO-5 / / AC device at different current densities. Its symmetry is excellent, and the basic shape does not change with the change of current density, indicating that the device has high coulombic efficiency and electrochemical reversibility. The current density of the calculated device is 1, 2, 4, 6, 8 and 10 A·g -1 The specific capacities are 112.1, 90.2, 65.1, 52.0, 42.7, and 34.7 F·g -1 .

[0085] (2) Power, energy density and cycle performance test

[0086] Performance indicators such as power, energy density and cycle stability are some of the factors that must be considered in the practical application of SCs. Fig. 9 (a) is the Ragone plot of NMMO-5 / / AC, comparing the power density and energy density with other devices. -1 , corresponding to a power density of 750W kg -1 , and its performance is better than many recently reported capacitors (as shown in Table 2). It can be seen that this three-dimensional network structure NMMO-5 assembled from two-dimensional porous sheets has excellent electrochemical properties.

[0087] Fig. 9 (b) is the NMMO-5 / / AC device cycle performance diagram. It can be seen from the figure that at 10A·g -1 After 10,000 charge-discharge cycles, the device capacity is 103% of the initial specific capacitance, while the coulombic efficiency is close to 100%, indicating the excellent cyclic reversibility of the device. It is worth noting that after cycling, the capacity increases slightly, reflecting the activation process of the electrode, which is probably due to the gradual infiltration of the electrolyte during the discharge process, exposing more active sites, thereby obtaining a higher specific capacitance.

[0088] Table 2 Comparison of electrochemical performance of supercapacitors assembled based on various MnMoO4 and its composite materials

[0089]

[0090] Finally, it should be pointed out that the above embodiments are only representative examples of the present invention. Obviously, the technical solution of the present invention is not limited to the above embodiments, and there are many variations. All variations that can be directly derived or associated with the content disclosed by ordinary technicians in this field should be considered as the protection scope of the present invention.

Claims

1. A method for preparing Fe, Co and Ni doped MnMoO4·H2O nano two-dimensional porous nanomaterial, characterized in that: Fe, Co and Ni doped MnMoO4·H2O nano-oxygen defect materials were prepared by template-free hydrothermal method in the absence of surfactant.

2. The method for preparing Fe, Co and Ni doped MnMoO4·H2O nano two-dimensional porous nanomaterial according to claim 1, characterized in that: The following steps are involved: (1) First, dissolve MnCl2·4H2O in distilled water and stir to obtain solution I; (2) dissolving Na2MoO4·2H2O in distilled water and stirring to obtain solution II; (3) taking solution II and solution I respectively, slowly adding solution II into solution I, and stirring to obtain a milky white solution III; (4) Add NiCl2·6H2O to solution III and stir to obtain solution IV; (5) Solution IV is transferred to a stainless steel autoclave and heated for reaction; after the reaction is completed, it is cooled to room temperature (natural cooling is sufficient), taken out and filtered, washed and dried to obtain Ni-doped MnMoO4·H2O product, which is labeled as NMMO-x; the Co and Fe doping amounts are prepared according to the Ni doping method and are labeled as FMMO-x and CMMO-x.

3. The method for preparing Fe, Co and Ni doped MnMoO4·H2O nano two-dimensional porous nanomaterial according to claim 2, characterized in that: The step (1) is specifically to take 3.4-4 mmol MnCl2·4H2O and dissolve it in 40-60 ml distilled water.

4. The method for preparing Fe, Co and Ni doped MnMoO4·H2O nano two-dimensional porous nanomaterial according to claim 2, characterized in that: The stirring in steps (1), (2) and (3) is magnetic stirring at a stirring speed of 400 to 700 rpm for 20 to 40 minutes.

5. The method for preparing Fe, Co and Ni doped MnMoO4·H2O nano two-dimensional porous nanomaterial according to claim 1, characterized in that: The step (2) is specifically to take 4 mmol·Na2MoO4·2H2O and dissolve it in 40-60 ml of distilled water.

6. The method for preparing Fe, Co and Ni doped MnMoO4·H2O nano two-dimensional porous nanomaterial according to claim 1, characterized in that: In the step (3), the volume ratio of solution II to solution I is (4-6): (4-6).

7. The method for preparing Fe, Co and Ni doped MnMoO4·H2O nano two-dimensional porous nanomaterial according to claim 1, characterized in that: The drying is performed at 40 to 80° C. for 8 to 16 hours.

8. The method for preparing Fe, Co and Ni doped MnMoO4·H2O nano two-dimensional porous nanomaterial according to claim 1, characterized in that: In the NMMO-x, x is Ni doping amount of 0%, 2.5%, 5% and 7.5%; in Co and Fe doping amount, x is 5%.

9. The method for preparing Fe, Co and Ni doped MnMoO4·H2O nano two-dimensional porous nanomaterial according to claim 1, characterized in that: The total amount of the MnCl2·4H2O and the transition metal salt was always kept at 4 mmol, and other conditions were not changed.

10. Fe, Co and Ni doped MnMoO4·H2O nano two-dimensional porous nanomaterial prepared by the preparation method of Fe, Co and Ni doped MnMoO4·H2O nano two-dimensional porous nanomaterial according to claim 1.